The Tree of Life, Book Three : The Cattle Cars Are Waiting, 1942-1944. - Rosenfarb, Chava (Madison : University of Wisconsin Press, 2006)
Winner of the 1972 J. J. Segal Prize and the 1979 Manger Prize for Yiddish Literature.
Intro -- Acknowledgements -- Chapter One -- Chapter Two -- Chapter Three -- Chapter Four -- Chapter Five -- Chapter Six -- Chapter Seven -- Chapter Eight -- Chapter Nine -- Chapter Ten -- Chapter Eleven -- Chapter Twelve -- Chapter Thirteen -- Chapter Fourteen -- Chapter Fifteen -- Chapter Sixteen -- Chapter Seventeen -- Chapter Eighteen -- Chapter Nineteen -- Chapter Twenty -- Chapter Twenty-one -- Chapter Twenty-two -- Chapter Twenty-three -- Chapter Twenty-four -- Chapter Twenty-five -- Chapter Twenty-six -- Chapter Twenty-seven -- Chapter Twenty-eight -- Chapter Twenty-nine...Thirty...Thirty-one...ad infinitum -- After the Voyage -- Glossary.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Holocaust, Jewish (1939-1945)-Fiction.; Jews-Persecutions-Fiction.; Electronic books